2022
DOI: 10.3390/membranes12050529
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun, Resorbable, Drug-Eluting, Nanofibrous Membranes Promote Healing of Allograft Tendons

Abstract: In spite of advances in medical technology, the repair of Achilles tendon ruptures remains challenging. Reconstruction with an autograft tendon provides the advantage of a higher healing rate; nevertheless, the development of donor-site morbidity cannot be ignored. We developed biodegradable, drug-eluting, nanofibrous membranes employing an electrospinning technique and evaluated their effectiveness on the healing of allograft tendons. Poly-D-L-lactide-glycolide was used as the polymeric material for the nanof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…For the same purpose, PLGA nanofiber pads doped with doxycycline were prepared and evaluated in vivo using a rabbit model. 124 As shown in Fig. 5f, this PLGA nanofiber pad provides continuous release of doxycycline for more than 42 days in vitro .…”
Section: Nanofibrous Scaffolds For the Healing Of Fibrocartilaginous ...mentioning
confidence: 82%
“…For the same purpose, PLGA nanofiber pads doped with doxycycline were prepared and evaluated in vivo using a rabbit model. 124 As shown in Fig. 5f, this PLGA nanofiber pad provides continuous release of doxycycline for more than 42 days in vitro .…”
Section: Nanofibrous Scaffolds For the Healing Of Fibrocartilaginous ...mentioning
confidence: 82%
“…To prepare the drug-loaded nano bers, a mixture of 93.3 mg each of teicoplanin, ceftazidime, and ketorolac was combined with 800 mg PLGA and 5 mL HFIP. The solution was spun using a laboratory-made spinning device [23]. The conditions were set as follows: voltage, 18 kV; ow rate of the mixture, 0.2 mL/h; and distance between nozzle and collection table, 15 cm.…”
Section: Electrospinning Of Drug-and Growth Factor-loaded Nano Bersmentioning
confidence: 99%
“…When poly-D-L-lactide-glycolide (PLGA) is used as the polymer material of the nanofiber membrane, doxycycline drug elutes the nanofiber membrane. Histological examinations and monitoring of postoperative animal activity levels have shown that the nanofiber membrane can promote the healing of tendon rupture, and can be used as an auxiliary tool for Achilles tendon homotransplantation and reconstruction surgery [ 66 ].…”
Section: Functional Electrospinning Products Of 3d Structures For Ten...mentioning
confidence: 99%